Sistem Monitoring Mesin Pengaduk Adonan Roti Otomatis berbasis Internet of Things (IoT) - Artono, Budi; Prakoso, Dimas Nur; Lestari, Tri Annisa Widya (Journal of Computer Science and Engineering (JCSE), 2023)
The purpose of this research is to develop an Internet of Things (IoT)-based automated bread dough mixing machine monitoring system using ultrasonic sensors and an integrated load cell sensor with a solenoid valve. The system is designed to control the distance between each bowl of dough ingredients and measure the weight of the mixed dough using a smartphone as the control interface. Additionally, the system allows users to issue on/off commands to the solenoid valve. This system provides detailed monitoring of the mixed blue dough ingredients. The research is conducted through several stages, including literature review, system design, hardware development, software development, implementation and integration, and testing. The testing phase involves both hardware and software components to ensure their functionality.